An entrepreneurial theory of the firm - Sautet, Frédéric E. (London ; New York : Routledge, 2000)
"Using an approach consistent with the modern Austrian School, Frederic Sautet brings a fresh perspective to the economics of the firm by developing the open-ended theories initiated by Mises and Hayek."
"An Entrepreneurial Theory of the Firm makes a thorough and comprehensive enquiry into the nature of the relationship that exists between firms and markets, with separate, in-depth explorations of both the existence and inner organization of the firm. Sautet develops a model that explains the emergence of the firm in the market process as the result of entrepreneurial activity in the context of genuine uncertainty and rivalrous competition. The Austrian angle enables him to provide a theory that is both alternative and complementary to established viewpoints."--Jacket
1. The Economics of the Firm, the Market Theory Problem and Transaction Cost Economics. The four rationales of the firm. The Market Theory Problem. The MTP and transaction cost economics. A brief assessment of two relevant alternatives to the transaction cost view. Are the above approaches sufficient? Conclusion: the MTP and beyond -- 2. The Lachmannian Problem, the Promoter and the Emergence of the Firm. On the importance of the prime mover: the entrepreneur. A view of the Lachmannian problem. The limits of the transaction costs perspective. A theory of the emergence of the firm: the exploitability thesis. Towards a solution to the Lachmannian problem. The distinctive nature of the firm.
Includes bibliographical references (pages 165-176) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Industrial organization (Economic theory); Transaction costs; Économie industrielle; Coûts de transaction; BUSINESS & ECONOMICS -- Economics -- Microeconomics; Industrial organization (Economic theory); Transaction costs; Unternehmenstheorie; Theory of the firm; Ondernemerschap; Transactiekosten